ACCURACY ASSESSMENT OF BIM-BASED AUTODESK REVIT FOR CONCRETE AND REINFORCEMENT QUANTITY TAKE-OFF IN BRIDGE STRUCTURES - Muhamad Aidil Fikri; Gunawan; Roma Dearni (RADJA PUBLIKA, 2026)
The development of Building Information Modeling (BIM) technology has accelerated digital transformation in the construction industry, particularly in improving the efficiency and accuracy of quantity estimation processes. However, Quantity Take-Off (QTO) calculations for bridge structures are still commonly performed using conventional methods, which are susceptible to human error and require considerable time. This study aims to evaluate the accuracy of BIM-based Autodesk Revit in estimating concrete and reinforcement quantities by comparing its results with conventional calculations on the Station VII B Bridge Project in Dumai City. A quantitative comparative approach was employed through three-dimensional modeling using Autodesk Revit 2024 and conventional quantity calculations based on Detailed Engineering Design (DED) documents. The resulting quantities were analyzed using Average Error and Root Mean Square Error (RMSE) to assess the level of agreement between the two methods. The results indicate that concrete quantity estimation recorded an Average Error of 1.455% with an RMSE value of 0.712 m³, while reinforcement quantity estimation showed an Average Error of 1.765% and an RMSE value of 0.016 m³. These findings demonstrate that Autodesk Revit is capable of producing quantity estimates that are highly consistent with conventional calculations while providing greater efficiency and reducing the potential for manual calculation errors. Therefore, Autodesk Revit can be considered a reliable alternative for Quantity Take-Off applications in bridge construction projects.